ANALISIS PENERAPAN GERAKAN LITERASI SEKOLAH PADA PEMBELAJARAN TEMATIK INTEGRATIF - Yusuf Yusuf; Oktiana Handini; Tabita Liana Kristiani (JURNAL SINEKTIK, 2020)
The purpose of this research is to find out 1) the application of the stages of the School Literacy Movement, 2) the impact of the implementation of the School Literacy Movement, 3) the spirit of learning of grade V learners through the School Literacy Movement. The research was conducted in grade V of Banjarsari Christian Elementary School Surakarta in the 2019/2020 School Year. Data collection method in this research is through in-depth interview, observation and documentation. Qualitative data validity checking technique is done by source trianggulation and technical trianggulation. The data in this study were analyzed in the order of data reduction, data presentation, conclusion drawing and verification. The results of the study: 1) The implementation stages of the School Literacy Movement in grade V students are at the stage of development with literacy programs such as Daily Musings "Quiet For a Moment", Saturday In Javanese Language, and scheduled literacy every Tuesday and Thursday conducted by each class. 2) The impact on integrative thematic learning of cognitive, affective, and psychomotor aspects of V-grade learners has increased. 3) The learning spirit of grade V learners has increased significantly.